Effectiveness of Local Food Based Supplementary Feeding Program in Improving the Nutritional Status of Pregnant Women with Chronic Energy Deficiency - Novia Nuraini; Rosita Syarifah; Aticeh Aticeh; Mulyana Mulyana (Jurnal Ners, 2026)
The nutritional status of pregnant women experiencing chronic energy deficiency (CED) is caused by inadequate family food consumption and food limitations. CED in pregnant women affects the baby and mother. The government is making efforts to overcome this by providing additional feeding (PAF) and mentoring to optimize nutritional intake so that nutritional status returns to normal. This study aims to empower the community through a program providing local food-based additional feeding for pregnant women with chronic energy deficiency. The type of research is an experimental one group study, targeting 71 pregnant women with CED who received local PAF, including respondents who were willing and received local PAF. The research analysis used a T-test for the results of the study.